2017
DOI: 10.1186/s13673-017-0123-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of a non-interactive talking avatar on social presence, credibility, trust, and patronage intention in an e-commerce website

Abstract: While prior research has examined the effects of interactive e-commerce avatars that simulate the roles of virtual assistants and recommender agents, there is lack of empirical study that investigates the effects of non-interactive talking avatars in e-commerce. This is unfortunate, as many websites today utilize non-interactive talking avatars that provide one-way dialogue in the forms of greetings, introduction of the company, and description of products and services offered. To bridge this gap, our study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…This results in a cognitive-based distrust mind-set being very fluid and context based, as well as consumer specific. Moreover, most existing research (Corbitt et al , 2003; Liew et al , 2017) argues for trust being critical for consumers’ patronage behavior. The current study suggests that cognitive-based trust (also referred to as social distrust by Hill and O’Hara, 2006; Mayo, 2015) and affective-based trust breaches are distinct from behavior and behavioral intent.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This results in a cognitive-based distrust mind-set being very fluid and context based, as well as consumer specific. Moreover, most existing research (Corbitt et al , 2003; Liew et al , 2017) argues for trust being critical for consumers’ patronage behavior. The current study suggests that cognitive-based trust (also referred to as social distrust by Hill and O’Hara, 2006; Mayo, 2015) and affective-based trust breaches are distinct from behavior and behavioral intent.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…When presenting information to consumers, the employment of anthropomorphic attributes increases information credibility (Holzwarth et al, 2006;Liew et al 2017) leading to lower perceived risk and reducing consumer uncertainty which is useful when learning about RNPs (Hoeffler, 2003;Castano and Giner-Sorolla, 2006). Learning theories within different frameworks support the employment of anthropomorphic attributes as a means of improving consumer comprehension (e.g.…”
Section: Really New Productsmentioning
confidence: 99%
“…In this study, 44 students interacted with the simulator and 15 observed the simulation due to limited space around the patient. There is evidence that learning outcomes are not strongly affected based on whether students interacted or observed the interaction [29].…”
Section: Participantsmentioning
confidence: 99%